Cooling is a cost-efficient way to adapt to heatwaves even in high-latitude cities - Hyyrynen, Matti; Ollikainen, Markku; Käyhkö, Janina; Suomi, Juuso; Lintunen, Jussi; Käyhkö, Jukka; Mäkelä, Antti; Gröndström, Fanny Marie; Juhola, Sirkku (Springer Science and Business Media LLC, 2025)
Heatwaves pose a direct threat to human health and well-being, particularly in cities, but there is little evidence of how much adaptation is needed at high northern latitudes. Drawing on IPCC's notion of climate risk, we develop an integrated approach to determine the economic viability of adaptation to growing mortality caused by increasing heatwaves via improved cooling of residential buildings. Accounting for the stochasticity of temperatures using Monte Carlo simulations, we estimate that the mortality will increase by tenfold relative to current mortality caused by heatwaves in Southern Finland. We carry out a cost-benefit analysis and show that adaptation to heatwaves via cooling is a feasible but costly solution in all studied cities and under all climate change scenarios. Given the high value of statistical life, lack of adaptation to increasing frequency of heatwaves would be costly to society. Adaptation to heatwaves by cooling is an effective solution: costs are 38 200 - 416 000 /life saved, and benefits exceed the costs by 1.8 to 18 times in alternative warming scenarios. Our results suggest that it is optimal to avoid any additional heatwave-related fatalities, implying that all the people belonging to the vulnerable population should be added to a district cooling network. The net present value of the adaptation by cooling is especially affected by the choice of the value of statistical life and more research is needed to ascertain the relevant value in the Finnish society.